The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1093/infdis/jiad324
|View full text |Cite
|
Sign up to set email alerts
|

Real-world Effectiveness of Molnupiravir and Nirmatrelvir/Ritonavir as Treatments for COVID-19 in Patients at High Risk

Dimitrios Paraskevis,
Maria Gkova,
Kassiani Mellou
et al.

Abstract: Background We aimed to evaluate the effectiveness of molnupiravir and nirmatrelvir/ritonavir in highly vulnerable SARS-CoV-2 patients using a retrospective cohort study design. Methods The impact of each drug was determined via comparisons with age-matched control groups of SARS-CoV-2-positive patients who did not receive oral antiviral therapy. Results Admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…The RCT data supporting the e cacy of Lagevrio® among unvaccinated patients were weaker than those of Paxlovid®, and its EUA was supported by a marginal vote. A recent registry-based study claimed a signi cant bene t, almost similar to Paxlovid®, especially among elderly patients, even after adjustment for vaccination status and time from last vaccine dose [7]. Nevertheless, the PANORAMIC clinical trial [29], where > 96% of patients were fully vaccinated, showed no difference in clinical outcomes between molnupiravir and usual care alone, similar to the results of a recent systematic review and metaanalysis [16].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The RCT data supporting the e cacy of Lagevrio® among unvaccinated patients were weaker than those of Paxlovid®, and its EUA was supported by a marginal vote. A recent registry-based study claimed a signi cant bene t, almost similar to Paxlovid®, especially among elderly patients, even after adjustment for vaccination status and time from last vaccine dose [7]. Nevertheless, the PANORAMIC clinical trial [29], where > 96% of patients were fully vaccinated, showed no difference in clinical outcomes between molnupiravir and usual care alone, similar to the results of a recent systematic review and metaanalysis [16].…”
Section: Discussionsupporting
confidence: 70%
“…Both nirmatrelvir/ritonavir (Paxlovid®) and molnupiravir (Lagevrio®) are FDA-approved for the treatment of COVID-19 based on the results of two randomized clinical trials (RCTs) from previous phases of the pandemic [4,5], with the latter being under emergency use authorization. Additionally, their effectiveness was con rmed in large retrospective registries, which included small proportions of immunosuppressed patients [6,7]. That being said, several groups [4,5,[8][9][10][11] have studied the bene cial role of those antivirals among eligible immunocompromised outpatients only, with relatively mixed results.…”
Section: Introductionmentioning
confidence: 99%
“…Nine studies (six peer-reviewed studies and three pre-prints) met all PICOTS criteria and were included in the SLR (Table 2 ) [ 29 – 37 ]. Two of the three pre-prints have subsequently been published as peer-reviewed articles [ 38 , 39 ]. The peer-reviewed version of Paraskevis et al .…”
Section: Resultsmentioning
confidence: 99%
“…As with sotrovimab, real-world studies have assessed the effectiveness of other available treatments during periods when Omicron subvariants have been predominant. A study in Greece among patients aged ≥65 years reported that both molnupiravir and nirmatrelvir/ritonavir significantly reduced the risk of hospitalisation and death compared with no oral antiviral therapy 36. The study included a period when Omicron subvariants BA.1, BA.2 and BA.5 successively predominated (December 2021 to July 2022).…”
Section: Discussionmentioning
confidence: 99%